Dietary Fat Modulation of Immune Function - Al-Khalaifah, Hanan; Al-Nasser, Afaf (Emerging Challenges in Agriculture and Food Science Vol. 7, 2022)
There has been some interest in the enrichment of poultry meat with long-chain n-3 polyunsaturated fatty acids (PUFA) to improve intakes of these fatty acids, which are currently well below the recommendations. However, there is some concern that diets enriched with n-3 PUFA have detrimental effects on chicken immunity and impair resistance to infection. The purpose of this chapter was to investigate the effect of dietary fat source and level on the immune function of broiler chickens, represented by Natural Killer (NK) cell activity. One-day-old male Cobb 500 broilers were fed on one of the four sources of n-3 PUFA: fish oil (FO)-, echium oil-, algal biomass, and flaxseed oil-enriched diets, as four treatments, at 50, 18, 18, and 19 g/kg, respectively. At slaughter, samples of blood and spleen were collected from twenty birds/treatment. Incorporating PUFA into rations fed to broiler chickens had a strong influence on the fatty acid composition of immune tissues. Natural killer (NK) cell activity was investigated. NK activity was highest in splenocytes and peripheral blood mononuclear cells (PBMCs) from broilers fed flaxseed oil, followed by those fed algal biomass or echium oil, and lowest for those from broilers fed FO. These results suggest that a DHA-rich algal product may enrich chickens with n-3 PUFA without significant detrimental effects on chicken immunity. Conclusively, this study contributed to the overall understanding of the influence of dietary n-3 PUFA on the immune function of broiler chickens. Such studies highlight the need for the poultry industry to consider the health status of poultry when poultry meat is being enriched with n-3 PUFA, especially EPA.